2009
DOI: 10.2135/cropsci2008.10.0585
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Advanced Cycle Breeding on Genetic Gain and Phenotypic Diversity in Barley Breeding Germplasm

Abstract: Abbreviations: QTL, quantitative trait locus; SSR, simple sequence repeat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“…It was reported (Martin et al, 1991;Condon et al, 2009) that traits like GY and DH are close to the target values. However, we still believe that drought tolerance and winter hardiness shoul d be used for genetic improvement and will benefit from additional genetic diversity.…”
Section: Genotypic Selectionmentioning
confidence: 78%
See 2 more Smart Citations
“…It was reported (Martin et al, 1991;Condon et al, 2009) that traits like GY and DH are close to the target values. However, we still believe that drought tolerance and winter hardiness shoul d be used for genetic improvement and will benefit from additional genetic diversity.…”
Section: Genotypic Selectionmentioning
confidence: 78%
“…studies within breeding programs can be used to assess the success of plant breeding strategies and their effects on the variation within breeding populations as a response to selection (Condon et al, 2009).…”
Section: Genotypic Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Closed panel comprises lines from the advanced cycle breeding program (elite × elite) with a relatively closed pedigree, i.e. , few new founders were introduced after 1958 when the strategy was initiated (Condón et al 2008; Condón et al 2009). The Reopened panel comprises lines from families derived from the introduction of 13 new donors to the Closed population in response to the FHB epidemic (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence and spread of this pathogen increased in the Midwestern United States in the early 1990s (McMullen et al 1997) and revealed limited genetic variation for disease resistance among existing barley cultivars and the need to introduce novel variation for resistance into breeding programs. During the 35 years preceding the FHB outbreak, the University of Minnesota barley breeding program made use of relatively closed pedigrees in an advanced cycle breeding scheme (Rasmusson and Phillips 1997) that primarily focused on crosses among elite lines from within the breeding population (Condón et al 2009). After the outbreak, numerous exotic sources of elite lines with known FHB resistance and reduced deoxynivalenol (DON) mycotoxin (which is produced by the pathogen) concentration were evaluated and introduced as parents in the breeding population to enhance FHB resistance (Smith et al 2013).…”
mentioning
confidence: 99%